ATPaseTb2, a unique membrane-bound FoF1-ATPase component, is essential in bloodstream and dyskinetoplastic trypanosomes. - Karolína Šubrtová; Brian Panicucci; Alena Zíková (PLoS Pathogens)
In the infectious stage of Trypanosoma brucei, an important parasite of humans and livestock, the mitochondrial (mt) membrane potential (Δψm) is uniquely maintained by the ATP hydrolytic activity and subsequent proton pumping of the essential FoF1-ATPase. Intriguingly, this multiprotein complex contains several trypanosome-specific subunits of unknown function. Here, we demonstrate that one of the largest novel subunits, ATPaseTb2, is membrane-bound and localizes with monomeric and multimeric assemblies of the FoF1-ATPase. Moreover, RNAi silencing of ATPaseTb2 quickly leads to a significant decrease of the Δψm that manifests as a decreased growth phenotype, indicating that the FoF1-ATPase is impaired. To further explore the function of this protein, we employed a trypanosoma strain that lacks mtDNA (dyskinetoplastic, Dk) and thus subunit a, an essential component of the proton pore in the membrane Fo-moiety. These Dk cells generate the Δψm by combining the hydrolytic activity of the matrix-facing F1-ATPase and the electrogenic exchange of ATP4- for ADP3- by the ATP/ADP carrier (AAC). Surprisingly, in addition to the expected presence of F1-ATPase, the monomeric and multimeric FoF1-ATPase complexes were identified. In fact, the immunoprecipitation of a F1-ATPase subunit demonstrated that ATPaseTb2 was a component of these complexes. Furthermore, RNAi studies established that the membrane-bound ATPaseTb2 subunit is essential for maintaining normal growth and the Δψm of Dk cells. Thus, even in the absence of subunit a, a portion of the FoF1-ATPase is assembled in Dk cells.